Kepemimpinan Humanistik dalam Upaya Meningkatkan Kinerja Guru di SMP Muhammadiyah 5 Surakarta - Ramadhan, Azrifvan Fakhri; Istanto, Istanto (Yayasan Rahmat Islamiyah, 2024)
Research on the principal's humanistic leadership in an effort to improve teacher performance aims to explain: 1) Implementation of the principal's humanistic leadership style; 2) The impact of the implementation of humanistic leadership style on teacher performance; 3) The obstacles of humanistic leadership in an effort to improve teacher performance. This research method uses qualitative research methods with descriptive nature. Data collection techniques used observation, interview and documentation methods. Data validity test using triangulation technique. Checking the validity of data by comparing data sources from observations and data from interviews. Data analysis was carried out through data collection, data reduction, data presentation, and conclusion drawing. From this research, it can be found and concluded that: 1) The leadership of the Principal of SMP Muhammadiyah 5 Surakarta in an effort to improve teacher performance uses a humanistic leadership style with the principal providing facilities and humane treatment, providing equal attention, dispatching teachers to Umrah, giving rewards and giving sanctions to teachers; 2) The impact of the principal's leadership in an effort to improve teacher performance, among others: Creating a good working atmosphere, Providing flexibility for teachers in conveying aspirations and Providing enthusiasm and appreciation for teachers; 3) The obstacles in the principal's leadership in an effort to improve teacher performance at SMP Muhammadiyah 5 Surakarta include: The principal sometimes does work that is not the realm of the principal, Lack of assertiveness from the principal, There is still forgiveness to the teacher and there is still a sense of reluctance to the teacher.Â